Sulfur Metabolism Pathways in Sulfobacillus acidophilus TPY, A Gram-Positive Moderate Thermoacidophile from a Hydrothermal Vent - Guo, Wenbin; Zhang, Huijun; Zhou, Wengen; Wang, Yuguang; Zhou, Hongbo; Chen, Xinhua (Frontiers in Microbiology, 2016)
Sulfobacillus acidophilus TPY, isolated from a hydrothermal vent in the Pacific Ocean, is a moderately thermoacidophilic Gram-positive bacterium that can oxidize ferrous iron or sulfur compounds to obtain energy. In this study, the sulfur metabolism pathways of S. acidophilus TPY with redox cycles were proposed via comparative transcriptomic analysis and confirmed by SOR overexpression in vivo and subsequent mRNA abundances analysis of sulfur metabolism related genes. Comparative transcriptomic analysis of this strain cultured in the presence of ferrous sulfate (FeSO4) or elemental sulfur (S0) was employed to detect differentially transcribed genes and operons involved in sulfur metabolism. The mRNA abundances of sulfur metabolism-related genes decreased when grown in S0 culture and increased in FeSO4 culture, which owed to sulfite reductase (SiR) involved in the dissimilatory sulfate reduction. Sulfur oxygenase reductase (SOR), whose mRNA abundances increased in S0 culture was suggested to play an important role in the initial sulfur oxidation. Sulfur metabolism pathways were proposed based on the transcriptome results. In order to confirm the pathways, overexpression of SOR in S. acidophilus TPY and subsequent mRNA abundances analysis of sulfur metabolism related genes were carried out. Conjugation-based transformation of pTrc99A derived plasmid from heterotrophic E. coli to facultative autotrophic S. acidophilus TPY despite their considerable differences in culture conditions was developed in this study. Transconjugation between E. coli and S. acidophilus was performed on modified solid 2:2 medium at pH 4.8 and 37 °C for 72 h. The selected recombinant S. acidophilus TPY-SOR had an SO42--accumulation increase, higher oxidation/ reduction potentials (ORPs) and lower pH than the wild type in the late growth stage of S0 culture condition. The transcribed level of sor gene in the recombinant strain increased in both S0 and FeSO4 culture conditions, which affected the transcription of other genes in the proposed sulfur metabolism pathways. Overall, the results significantly expand our understanding of sulfur metabolism within the Sulfobacillus genus and provide a successful gene manipulation method.